A history of the county court, 1846-1971 - Polden, Patrick (Cambridge studies in English legal history., 1999)
The first full account of the establishment of the County Court in 1846 and its work, through to its reconstruction in 1971. It traces its development from being largely a debt collection agency through to its ultimately far wider jurisdiction as the main forum for most civil disputes.